Tinnitus and taste disturbances reported after myringoplasty: Data from a national quality registry. (3rd October 2018) - Berglund, Malin; Suneson, Petter; Florentzson, Rut; Fransson, Mattias; Hultcrantz, Malou; Westman, Eva; Eriksson, Per Olof
Abstract : Objectives/Hypothesis: Postoperative tinnitus and taste disturbances after myringoplasty are more common than previously reported. Study Design: This study was a retrospective analysis of prospectively collected data from the Swedish National Quality Registry for Myringoplasty. Methods: The analysis was performed on extracted data from all counties in Sweden collected from database A from 2002 to 2012 and database B from 2013 to 2016. Tinnitus and taste disturbance complications 1 year after myringoplasty were analyzed in relation to gender, age, procedure, and success rate. In database A, physicians reported tinnitus and taste disturbances. In database B, patients reported the complications. Results: A major difference was found when the complications were reported by physicians compared to when the complications were reported by patients. In database A, tinnitus was reported in 1.2% of the patients and taste disturbances in 0.5%. In database B, the frequencies were 12.3% and 11.2%, respectively. Tinnitus and taste disturbances were more frequent after conventional myringoplasty compared to those after fat grafting and were more frequent after primary compared to those after revision surgery when reported by physicians. Patients, however, reported the same frequency of tinnitus after fat graft myringoplasty compared to that after conventional myringoplasty (12.0% vs. 12.6%) and fewer taste disturbances after revision surgery. In follow‐up assessments, complications persisted after surgery over a long time period. Conclusion: Tinnitus and taste disturbances are more common after myringoplasty when patients report their symptoms than when physicians report the symptoms. Level of Evidence: 2b Laryngoscope, 129:209–215, 2019